(untitled) (Bioresearch Communications, 2024)
Background and Objectives: Estimation of nutrient content of a recipe by a recipe calculation method may be cost‐effective and alternative to the chemical analysis for a range of applications, laboratory analysis of standardized recipes is considered a more authentic and accurate source of recipe nutrient data. Food composition data (FCD) regarding festival foods and dishes is very scanty in local and global food composition tables (FCT). The present study, thus, conducted a recipe survey on the ingredient profile of festival recipes consumed by lower to middle-income households in Bangladesh followed by proximate analysis of standard recipes obtained by collapsing similar recipes. Unanalyzed nutrients were obtained by data compilation from local and global food composition databanks (FCDB). Methodology: A cross-sectional recipe survey was conducted sequentially on festival foods and dishes among purposefully selected housewives residing at different areas of Dinajpur district and Dhaka city. The study instrument was a structured pre-tested questionnaire. Nine homemade festival recipes out of 40 recipes cited viz., plain polao, beef bhuna, fish fry, chicken bhuna, payesh, beef biriyani, chinese vegetable, chicken roast and baked fish were selected and standardized according to the method established in our laboratory. The selected recipes were prepared and analyzed for proximate composition along with an estimation of the cooking yield factor. Content of moisture, ash, protein, total fat, total dietary fiber (TDF), available carbohydrates, and calorie values of nine selected dishes were determined using standard operating procedures (SOP) established on the basis of AOAC methods. Precision and accuracy of analytical values were checked as part of Quality Assurance Program (QAP). Data compilation of missing values for vitamins and minerals was conducted according to FAO data compilation toolkit. Result: Moisture content ranges from 30.42-70.75%, protein content ranges from 2.60-35.70%, fat content ranges from 2.61-22.53%, ash content ranges from 0.6241-8.8%, TDF ranges from 0.58-8.49%, carbohydrates ranges from 0.65-45.7% and energy content ranges 101.5-368.4 kcal/100g fresh sample. The cooking yield ranges from 40.96-96.82%, which is highest in plain polao and lowest in fish fry. Conclusion: The data generated from this study can be used as reliable data which will enrich the national food composition table. Bioresearch Commu. 10(2): 1516-1523, 2024 (July)